Rewaste Innovation at The Friendship Center General Hospital - Nemi Muhaeminah (Green Publisher Indonesia, 2025)
This research aims to implement waste management innovations at the Central Friendship General Hospital through the development of compost, biopore infiltration holes, and reuse of plastic waste. The hospital produces around 10,000 tons of domestic waste per year, so a solution is needed to minimize this waste. This innovation involves making compost from organic waste such as leaves and vegetable scraps which are processed into organic fertilizer. Biopore infiltration holes are used to reduce organic waste and maximize water absorption, while broken plastic waste is reused as plant pots. The results of the study show that this innovation not only succeeds in significantly reducing waste, but also provides cost efficiency that has a positive impact on hospitals.